Normalising the 'alter-Europe' or going beyond this Europe? Italian environmental movements' perspectives on Europe, democracy and the ecological crisis. Issue 3 (2nd July 2020) - Bertuzzi, Niccolò
ABSTRACT: Based on 19 interviews with key activists, the paper discusses different visions of Europe and democracy within the Italian environmental archipelago. A clear dichotomy has emerged. On the one hand, institutional ENGOs conduct lobbying activities, adapting to different multilevel political opportunities: their attempt is to reform the current structure of the EU, which also contributes to institutionalise the innovative perspectives of 'another Europe' advanced by the Global Justice Movement in the early 2000s. On the other hand, grassroots groups suggest going 'beyond this Europe', as they are critical of its current geographical borders and political institutions. They normally do so by adopting contentious actions in a domestic dimension. Furthermore, two divergent democratic paradigms can be identified. I propose to call them ecological democracy and green democracy. The latter stands for a conception of the environmental issues as subordinated to, or at least unthinkable outside, the (Western) representative democracy and the gospel of economic growth. Ecological democracy involves a conception of democracy as effective only if based on ecological perspectives, within a vision which stigmatises capitalist economy and the institutions supporting it. These paradigms resonate with the interpretation of the current (ecological) critical juncture as the Anthropocene or as the Capitalocene.